Upaya peningkatan hasil belajar siswa dalam pembelajaran daring melalui penerapan model problem based learning siswa kelas IV SD Negeri Sambeng tahun 2020/2021. Jurnal Kualita Pendidikan - Ismiyono Ismiyono (Jurnal Kualita Pendidikan, 2020)
The purpose of this study was to improve student learning outcomes through the Problem Based Learning learning model for fourth-grade students of SD Negeri Sambeng. The type of research used is PTK. The research subjects were grade IV students. Data collection techniques using tests and observation results. The data analysis technique used is in the form of qualitative data and quantitative data. Pre-action learning outcomes of students who passed were only 5 students with a percentage of 33.33% then in cycle I increased to 7 students with a percentage of 46.67% and in cycle II increased to 12 students with a percentage of 80%. Thus, the application of the Problem Based Learning learning model can improve the learning outcomes of fourth-grade students of SDN Sambeng.